Reactive Vaporization of Crude Glycerol in a Fluidized Bed Reactor - Sereshki, B. Rafii; Balan, S.-J; Patience, G. S; Dubois, J.-L (Industrial & engineering chemistry research, 2010)
Crude glycerol is a coproduct of the trans-esterification of vegetable oil and animal fat to biodiesel that contains as much as 5% salt. Processing the glycerol to value added products often requires an expensive distillation step. In this work, we propose a new process in which crude liquid glycerol is fed directly to a fluidized bed, vaporizes, and then reacts to form acrolein over a tungsten doped zirconia catalyst. Salt in the crude glycerol crystallizes and accumulates in the fluid bed. In a commercial process, the salt crystals will be subject to significant mechanical stresses that will cause them to attrit. The attrited powder will be elutriated from the bed and collected by filters. The focus of this work has been to evaluate the effect of salt on catalyst activity as well as its attrition resistance. Thus far, there is little evidence of salt crystallization or migration to the interior of the catalyst particlesafter more than 1 day of continuous operation, catalyst activity remained unchanged. Tests on a standard air jet mill suggest that the mechanical stresses typical of a fluidized bed will be sufficient to attrit the salt and thus minimize its accumulation in the reactor with time.